Proses Perumusan Kebijakan Pemekaran Daerah (Studi di Pulau Sebatik Kabupaten Nunukan Kalimantan Utara) - Febriyandi, Didi (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
Expansion of the area if done a noble thing to reduce inequalities in public services and the welfare of society, especially in the border region Sebatik Island which is directly adjacent to the State Malaysia. In the process of formulation has traversed a long way from 2005 to 2015 Sebatik not yet bloomed. By rule Sebatik already complied with the procedures then to the center stage and for reasons that remain unclear policy process has not reached the desired goal together. As for the role of local actors has attempted to influence that although the outline deal happens area due to political factors to the division process to the center stage. It's just less escort and intensive communication on the elite center.